0500 Evaluation of the Human Abuse Potential of Single Oral Doses of V117957, a Novel, Highly Potent and Selective Partial Agonist for Nociceptin/Orphanin-FQ Peptide (NOP) Receptors. (27th May 2020) - Harris, S; Zhou, M; Cipriano, A; Kapil, R; Shet, M; He, E; Apseloff, G
Abstract: Introduction: The satisfactory safety/tolerability profile of V117957, an investigational NOP receptor partial agonist, has been previously established in ~200 healthy subjects with maximum doses at 30mg following a single oral administration and 10mg once daily for 2 weeks. V117957 exhibited linear plasma exposures at doses up to 10mg. In patients with insomnia disorder, V117957 demonstrated dose-dependent improvement in sleep efficiency and sleep maintenance between 0.5mg and 10mg as measured by polysomnography and patient diaries. The current study evaluated the abuse potential and safety of V117957 in healthy, nondependent recreational polydrug users with a history of central nervous system (CNS) depressant use. Methods: The abuse potential of V117957 (1mg, 6mg, 10mg), placebo, and triazolam (0.5mg, 1mg) were assessed in a randomized, double-blind, double-dummy, placebo- and positive-controlled crossover study. Triazolam was utilized as a positive control based on its comparable pharmacokinetic and pharmacodynamic characteristics. V117957 doses (1mg, 6mg, 10mg) were selected to represent therapeutic, mid-range supratherapeutic, and maximum-tolerated supratherapeutic doses, respectively. Subjects were qualified based on pharmacodynamic responses following a single oral 0.75mg triazolam dose. Drug liking was measured through 24 hours, including the primary endpoint of maximum "at the moment" Drug-Liking Visual Analog Scale, as recommended by FDA. Secondary endpoints included Divided Attention Test (DAT) and Choice Reaction Time (CRT). Results: The positive control (triazolam 0.5mg, 1mg) produced statistically significant greater abuse potential and cognitive/motor impairment versus placebo, which demonstrated study validity. In contrast, V117957 at 1mg was not statistically significantly different from placebo. At the supra-therapeutic doses of 6 and 10mg, V117957 was associated with abuse potential and cognitive/motor impairment greater than placebo, yet similar to those of triazolam 0.5 and 1mg. Conclusion: Overall, in this valid study, V117957 1mg and placebo were associated with statistically significant lower potential for abuse and reduced cognitive/motor impairment compared with the two supratherapeutic doses of V117957 (6mg, 10mg), and triazolam (0.5mg, 1mg). V117957 1mg met FDA's statistical criterion for similarity to placebo. Support: Funded by Imbrium Therapeutics, a subsidiary of Purdue Pharma L.P.